MIC leaders must change approach, says Saravanan - Daily Express, (KK) (Daily Express (KK), 2013)
KUALA LUMPUR: MIC leaders need to change their approach by becoming more vocal in addressing the needs of the Indian community, said party Vice-President Datuk M. Saravanan.